Systematics and evolution of Chresta Vell. ex. DC. (Vernonieae, Asteraceae) - Siniscalchi, Carolina Moriani (2018)
Chresta belongs to tribe Vernonieae, subtribe Chrestinae, and presents eighteen species distributed in the Caatinga, Cerrado and Mata Atlântica domains. Its species display a fairly wide range of characters that led the species to be ascribed to several distinct genera, sometimes also classified into different groups inside the tribe. Attempts to define the position of the genus in relation to other Vernonieae subtribes and to understand the relationships within the genus have so far been unsuccessful. In this work, we present a novel phylogeny for Chresta, based on a complete set of sampled taxa from which hundreds of molecular markers were assessed, and for the first time, phylogenomics methods are applied to a Neotropical group of Asteraceae. We confirm the monophyly of Chresta and resolve infrageneric relationships with high support for all clades. We also successfully define the sister group to the genus, although the relations of this whole lineage with Lychnophorinae and Lepidaploinae are still doubtful, and. We use the obtained trees to reconstruct ancestral states of ten selected characters, which seem to have played an important role during the history of the genus, and propose a biogeographical scenario where the diversification of the group may have taken place. We also use evidence from microsatellite markers to study the population genetics of five species from the Caatinga that naturally present isolated populations restricted to narrow rupiculous habitats. These species present contrasting patterns, varying in their degree of genetic diversity and structuring, and this data enable us to discuss the relative impact of factors such as spatial distance, substrate preference, population size and dispersal ability on the genetic flow among the populations assessed. We also present an illustrated synopsis of the genus, with a new phylogenetic infrageneric classification, summarizing the accumulated knowledge about Chresta so far. We provide descriptions of four new species, a key for identification of 18 accepted species and three infrageneric taxa, synonyms, illustrations and distribution maps of the species, as well as their current conservation status